The Role of Student Engagement in Innovation and University Entrepreneurship: Evidence from a Private University in Lima - Olórtegui Alcalde, Luis Miguel; Saldaña Narro, Julio Brayan; Gasparrini Cañas, Víctor Gerardo; Marcelo Quispe, Luis Alberto (LACCEI, 2025)
This study examines the impact of student engagement on innovation and entrepreneurship at a private university in South Lima. A quantitative approach was employed, utilizing the partial least squares structural equation modeling (PLS-SEM) method within a non-experimental design. The study evaluated a sample of 385 students with experience in active entrepreneurial ventures. The findings indicate that student engagement significantly influences creativity (β = 0.67, p < 0.001) and the generation of innovative ideas (β = 0.61, p < 0.01), underscoring its impact on the development of entrepreneurial competencies. Additionally, key barriers were identified, including a lack of practical knowledge (41%), time constraints (34%), and limited access to technological resources (28%), which hinder the effective implementation of innovation and entrepreneurship strategies. To address these challenges, educational strategies such as innovation labs, interdisciplinary programs, and active learning methodologies that foster student participation are proposed. The study also highlights policy implications, emphasizing the need to strengthen collaborations between universities, the private sector, and governments to ensure access to resources and training in advanced methodologies. In conclusion, despite existing challenges, student engagement emerges as a key driver of sustainable innovation and the university entrepreneurial ecosystem, with a significant impact on the training of future entrepreneurs and regional economic development.